Story of being useless & Three contexts of a writer : two novellas - Dongare, Avadhoot; Khan, Nadeem (tr.) (Delhi Ratna Books, 2019)
News! How much newness does any news have? What news-value do the non-new things carry? There are things, incidents and people that do not make news. They do not possess enough newness for the news-hungry world. These things and beings are useless for the manufacturers of news.
Keywords: English Fiction; Marathi fiction -- Translations into English; Translations